Asymmetric Catalysis with CO2: The Direct α‐Allylation of Ketones. Issue 20 (13th April 2016) - Pupo, Gabriele; Properzi, Roberta; List, Benjamin
Abstract: Quaternary stereocenters are found in numerous bioactive molecules. The Tsuji–Trost reaction has proven to be a powerful C−C bond forming process, and, at least in principle, should be well suited to access quaternary stereocenters via the α‐allylation of ketones. However, while indirect approaches are known, the direct, catalytic asymmetric α‐allylation of branched ketones has been elusive until today. By combining "enol catalysis" with the use of CO2 as a formal catalyst for asymmetric catalysis, we have now developed a solution to this problem: we report a direct, highly enantioselective and highly atom‐economic Tsuji–Trost allylation of branched ketones with allylic alcohol. Our reaction delivers products bearing quaternary stereocenters with high enantioselectivity and water as the sole by‐product. We expect our methodology to be of utility in asymmetric catalysis and inspire the design of other highly atom‐economic transformations. Abstract : While indirect approaches are known, the direct catalytic asymmetric α‐allylation of branched ketones has been elusive until today. By combining "enol catalysis" with the use of CO2 as a formal catalyst, a solution to this problem was developed and a direct, highly enantioselective and highly atom‐economic Tsuji–Trost allylation of branched ketones with simple allylic alcohol is reported.